Participation of the Intercostal Nerves to the Innervation of the Diaphragm Muscle in Cavia porcellus - de Faria, Marcelo Domingues; Gradela, Adriana; Santos, Ana Caroline dos; Lopes, Ítalo Barbosa Lemos; Inoue, Vanessa Souza; Brito, Bárbara Conceição Vilas Bôas Marques (Journal of Morphological Sciences, 2019)
Introduction The diaphragm is the leading respiratory muscle. It is innervated mainly by the diaphragmatic nerve, and, in some species, by the delicate fibers of the intercostal nerves. In guinea pigs, there is no description of these anatomic structures that innerve this important muscle. This study aimed to analyze the participation of the intercostal nerves to the innervations of the diaphragm of guinea pigs of both sexes.Materials and Methods We studied 40 guinea pigs (Cavia porcellus) of both sexes. We fixed and dissected the diaphragm of the specimens used in the experiment to assess the path of the intercostals nerves in both the body antimeres.Results The diaphragm was innervated by the intercostal nerve pairs 6 through 12, and, less frequently, by the 8th nerve (38/40 = 95%), followed by the 7th (36/40 = 90%) and subsequently by the 9th (32/40 = 80%). The 12th nerve presented the lowest frequency (2/20 = 10%) in both genders. All nerve pairs displayed similar occurrence compared with the gender and the antimeric disposition. The only exception was the 9th nerve, which presented a significant variation of the occurrence, both in relation to gender and antimeric disposition. From a statistic point of view, all nerves were independent. We observed no correlation between the gender and their position.Conclusions We shall conclude that the diaphragm of guinea pigs is innervated by the 6th through 12th pairs of intercostal nerves, with the 7th, 8th, and 9th being the primary providers. There is no interference of the variables gender or antimeric disposition on the behavior of the intercostal nerves of guinea pigs as refers to their origin and participation to the innervations of the diaphragm.
Keywords: guinea pig; diaphragmatic muscle; innervation